A PANEL DATA ANALYSIS OF FACTORS PUSHING GDP OF MALAYSIA: A RESEARCH ON SELECTED ECONOMIC INDICATORS - Monika Chopra (IQTISHADUNA, 2021)
Introduction: From time immemorial, the policy emphasis has always been on Gross Domestic Product (GDP) since it is the measure of wellbeing. Every country's budget is intended to move the economy in the right direction by promoting economic development. Objective: The study is performed to analyse the long-term impact of select economic indicators from available literature review on economic growth of Malaysia. Methodology: For meeting the research objective a panel data is famed through data collection from official website of world bank. After collecting data of selected indicators, research tools namely- mean, standard deviation, ANOVA and regression are applied. Value: The study will lead to an understanding of which important element affects GDP and allows the policymakers to focus their attention on factors relevant to the goal of raising GDP.